Impact of automotive tax incentives during Covid-19: Evidence from Indonesia - Sukaryo; Hariyanto, Sigit (Directorate General of Taxes, 2024)
In 2021, as part of the Pemulihan Ekonomi Nasional/ National Economic Recovery (PEN) program, the government introduced additional tax incentives to boost durable goods consumption, the PPnBM incentives, for qualified new car purchases. This study aims to explore the PPnBM incentives’ impact on automotive sectors in 2021, utilizing the Interrupted Time-Series Analysis (ITSA) methodology and seasonal forecasting method with Holt-Winters exponential smoothing and Autoregressive Integrated Moving Average (ARIMA) for four years from 2018 until 2021. In particular, using the automobile wholesales and tax administration data, this paper assesses the impact of the PPnBM incentives on car wholesales, participating firms’ sales, purchases, and wage expenditure. The impact of the PPnBM incentives on automotive sectors in 2021 suggested no significant difference in incentives-qualifying cars’ wholesales before and after the PPnBM incentives. However, the impact of the PPnBM incentives on total sales recovery resulted in the incentive participants recovering their total sales to the pre-Covid-19 level. In general, from the variables tested, the result suggests that the PPnBM incentives had a modest impact on wholesale recovery and economic activity for participating automotive manufacturers during the incentives period.